Organizational Relations and Human Resources with Information Quality in Health Center Information System Operators - Jefri, Amar; Sunarsih, Sunarsih; Tasnim, Tasnim (Waluya The International Science of Health Journal, 2023)
Backgrounds: Preliminary studies found that the low quality of information in the implementation of the Health Center Information System was caused by the absence of a Health Center Management Information System management team, lack of knowledge and human resource capabilities, lack of funding and specific guidance on Health Center Information System Software operations and lack of use of technology such as computers in processing input, data processing and information output. So that it attracts researchers to conduct research on the Quality of Information on Health Center Information System Operators. Methods: This research is a quantitative research, with a Cross Sectional Study design. The population in this study were 36 people with a total sample of the Health Center Management Information System management team in East Kolaka, namely 36 people with a proportion of 3 people. Each Community Health Center used a non-probability sampling technique in determining the sample. Results: The results of the chi square statistical test at the level of confidence show that the value of p = 0.002 and the calculated X2 value = 9.257 > the X2 table value = 3.841, which means there is a relationship between Organization and Information Quality. And the results of the chi square statistical test show that the value of p = 0.04 and the calculated X2 value = 4.050 > the X2 table value = 3.841, which means that there is a relationship between Human Resources and Information Quality. Conclusion: There is a moderate relationship between Organization and Information Quality and there is a weak relationship between Human Resources and a moderate relationship between Information Quality in the Implementation of Health Center Information Systems in East Kolaka Regency.